The Influence of Spirit and Morale of Indonesian Navy Soldiers on Performance in the Amphibious Ship Unit of Koarmada - Rizky Wiradiputra; Sri Umiyati; Sulistiyanto (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to test and analyze the influence of morale on performance, soldier morale on performance, and soldier morale simultaneously on performance in the Amphibious Ship Unit (Satfib) of Koarmada I, which is still not optimal. This research used a quantitative method with a proportional random sampling technique from 623 Satfib soldier personnel consisting of officers, non-commissioned officers, and enlisted personnel. The data collection method was carried out using a list of questions. The data analysis method was multiple linear regression analysis with the Special Package for Statistics Science (SPSS) version 24 application. This research also used validity and reliability test results as well as hypothesis testing results by research standards. The research results show that: the soldier's morale variable has a positive and significant effect on the performance variable. The variables of soldier spirit and morale simultaneously have a significant effect on personnel performance with a contribution of 0.420 or 42.0%. This means that the exogenous variable consisting of the spirit and morale of soldiers provides almost all the information needed to predict variations in the endogenous variable (performance) of 42.0%, thus there is still 58.0% influenced by other factors not examined in this research. It is hoped that Satfib Koarmada I can increase the enthusiasm and morale of soldiers so that it can create a more conducive working atmosphere so that it is hoped that it can improve performance to achieve organizational goals optimally